Eye morphology and visual acuity in the pipevine swallowtail (Battus philenor) studied with a new method of measuring interommatidial angles. (5th October 2015) - Bergman, Martin; Rutowski, Ronald L.
Abstract : Because of the important role sensory systems play in the behaviour of animals, information on sensory capabilities is of great value to behavioural ecologists in the development of hypotheses to explain behaviour. In compound eyes, interommatidial angles are a key determinant of visual acuity but methods for measuring these angles are often demanding and limited to live animals with a pseudopupil. Here we present a new technique for measuring interommatidial angles that is less demanding in terms of technology than other techniques but still accurate. It allows measurements in eyes without a pseudopupil such as dark eyes or even museum specimens. We call this technique the radius of curvature estimation (RCE) method. We describe RCE and validate the method by comparing results from RCE with those from pseudopupil analysis for the butterfly Asterocampa leilia . As an application of RCE we measure the eyes of the butterfly Battus philenor, a species whose visually guided behaviour is well known but whose eye structure and visual acuity are unknown. We discuss the results of the eye morphology in B. philenor in relation to their behaviour and ecology. We contend that RCE fills a gap in the repertoire of techniques available to study peripheral determinants of spatial resolution in compound eyes, because it can be applied on species with dark eyes. RCE then opens up for sampling a larger number of specimens, which, in combination with being able to use museum specimens, makes it possible to quantitatively test ecologically and evolutionarily driven hypotheses about vision in animals in a new way.